Mutation of TBC1 Domain containing kinase (TBCK) with associated intellectual disability and hypotonia - Prem Chand; Sulaiman, Asna; Kirmani, Salman (Journal of the Pakistan Medical Association, 2023)
Infantile Hypotonia with Psychomotor Retardation and Characteristic Facies-3 (IHPRF-3) Syndrome is a rare pathology occurring due to mutations in the TBC1 domain containing kinase (TBCK). This is a neurodevelopmental disorder presenting with a neurological and dysmorphic feature including intellectual disability, limb and craniofacial abnormalities. We present a case of TBCK mutation of the variant (p.Gln164*), present on Exon 6; this sequence change creates a premature translational stop signal (p.Gln164*) in TBCK, creating a disrupted protein leading to a loss of function. This variant has not yet been reported in genetic databases. We need to establish a better understanding of this disorder by reporting these novel genetic mutations so that these complex patients can be successfully managed by multidisciplinary teams. Keywords: Infantile hypotonia, Intellectual disability, Gene mutation.